Besarnya Penyusutan Yang Terjadi Pada Peleburan Logam Non-Fero Dengan Menggunakan Bahan Baku 2.5 Ton Logam Untuk Pembuatan Komponen Boiler Pada Tanur Kupola Di PT. X - Darmadi, Herry; Dewatmoko, Muhammad Andika; Kurnia, Dian; Bintang, Nurul Shadrina (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2025)
The casting industry is a kind of mining industry, where all industry manufacturing would never exist without the casting of the casting industry, much more difficult for the economy of a country without its own industrial role. A brushwork furnace that is one of the most popular types of metal smelting kitchens. The large shrink that occurs at smelting metals for making boiler components using 2.5 tons of raw materials is 15.08 percent or weighing 2,123 kg. the foundry in PT X using cocash-fuel (coal with high carbon levels). The process of smelting metals included sand prints that served the desired components, supplying raw materials and fuel to suit needs, smelting the kiln in my furnace with the help of blowers, pouring the molten metal into the ground, and cooling the molten metal.